Upaya Penguatan Menajemen Keuangan Bumdes Lentera Kabuna - Petrus Ans Gregorius Taek (Program Studi Ilmu Politik Fakultas Ilmu Sosial dan Ilmu Politik Universitas PGRI Ronggolawe Tuban, 2024)
The financial management of an institution needs to be managed accountably and transparently so that the institution can continue to develop from various aspects. It is very necessary to have good and correct financial management of BUMDes Bersama so that it can become the driving force of the village economy. BUMDes financial management must be based on the principles of transparent, accountable, participatory village financial management, as well as orderly and budgetary discipline. (Suryo Wibowo & Sulistya Hapsari, 2022). In this case, one effort to increase understanding of Bumdes Kabuna's financial management is to take part in financial literacy training from the Ministry of Villages, Development of Disadvantaged Regions and Transmigration. Bumdes Lentara Kabuna, located in Kakuluk Mesak District, Belu Regency, has succeeded in managing its finances well and transparently and has increased the progress of the institution. The Kabuna Village Government continues to support Bumdes in every way, one of which is through training to increase the capacity of Bumdes administrators organized by the Ministry of Villages in collaboration with the Belu Regency Social Service. The training was carried out as a form of effort to improve Bumdes financial management so that all forms of Bumdes financial transactions can be accounted for administratively and legally. The problems faced by Bumdes Lentera are the form of financial reporting that continues to change and the availability of human resources that are not in accordance with the financial sector, so training is very necessary. Through this training, the human resources of administrators can be improved and their skills in managing BUMDes finances can continue to be updated according to the nomenclature in the Ministry of Villages. The methods used in the training were talk shows, Focus Group Discussions (FGD) and presentations. The aim and hope of this training is that participants will be able to prepare financial administration properly and correctly according to regulations to the maximum extent.